Targeting the Hypoxic and Acidic Tumor Microenvironment with pH-Sensitive Peptides - Dharmaratne, Nayanthara U.; Kaplan, Alanna R.; Glazer, Peter M. (Cells (Basel, Switzerland), 2021)
The delivery of cancer therapeutics can be limited by pharmacological issues such as poor bioavailability and high toxicity to healthy tissue. pH-low insertion peptides (pHLIPs) represent a promising tool to overcome these limitations. pHLIPs allow for the selective delivery of agents to tumors on the basis of pH, taking advantage of the acidity of the hypoxic tumor microenvironment. This review article highlights the various applications in which pHLIPs have been utilized for targeting and treating diseases in hypoxic environments, including delivery of small molecule inhibitors, toxins, nucleic acid analogs, fluorescent dyes, and nanoparticles.